The Variety of Cello Playing Styles in the Keroncong Community in Pacitan - Azfar, Adimas Akma Danish; Rachman, Abdul (Program Studi Pendidikan Musik, 2025)
The cello is a musical instrument that plays a vital and distinctive role in the keroncong music ensemble, primarily as a rhythm keeper during the performance. Nowadays, the way the cello is played in keroncong seems to have evolved. Many young artists are now trying to develop their playing style in new directions, such as by adapting it to other music genres. This indicates that playing the cello in keroncong is not static but continues to evolve alongside changing musical tastes, advancements in technology, and socio-cultural factors, leading to a variety of playing styles among its musicians. The keroncong community in Pacitan experienced this same trend: artists from different generations interact, blend, and create diverse playing styles. This study aims to identify the various cello playing styles within the keroncong music community in Pacitan. The research method is qualitative, employing a musicology approach. Data were collected through observation, interviews, and document review, with data triangulation used for analysis. The findings show that keroncong cello playing goes beyond traditional practices, shaped by social experiences, cross-genre influences, and each artist's role in the local keroncong scene. The study concludes that keroncong cello styles are varied, reflecting each artist's musical interpretation and evolving according to socio-cultural changes.